PENGARUH MEDIA EDUKASI ULAR TANGGA “SERU” TERHADAP PENGETAHUAN KONSUMSI BUAH DAN SAYUR PADA ANAK PRA SEKOLAH DI PAUD KOTA CIMAHI (Jurnal Kesehatan Siliwangi, 2023)
Background: Developing countries in the health sector are undergoing epidemiological transitions including degenerative diseases. Degenerative diseases can occur, one of which is due to lifestyle changes such as reduced public interest in consuming fruits and vegetables. According to Riskesdas data in 2018 in Indonesia, the lack of fruit and vegetable consumption in the population aged ≥5 years is 95.5%, West Java is 98.8% and Cimahi City is included in the city that is still low in fruit and vegetable consumption. Purpose: Knowing the influence of the snakes and ladders educational media "SERU" on the knowledge of fruit and vegetable consumption in pre-school children at PAUD Cimahi City. Methods: This study used a quasy experiment design with a one-group pretest-posttest design with a sample (total sampling) of 32 students. Data analysis using Paired T-test. Results: The average knowledge score of respondents before being given the intervention was 50.65 and the average knowledge score of the respondents after being given the intervention was 71.78. There was an increase in knowledge by 21,13. The p value in this study was (p = 0.000), the influence of the snakes and ladders educational media "SERU" on knowledge of fruit and vegetable consumption, because the snakes and ladders media has the advantage of being fun so that children are interested in learning while playing, effective for knowledge review, very fond of being full of color, and can motivate them to continue learning. Conclusion: The influence of the snakes and ladders media "SERU" on the knowledge of fruit and vegetable consumption in pre-school children at PAUD Cimahi City.